Single-cell RNA sequencing uncovers dynamic roadmap during chicken spermatogenesis - Haishan Guo; Jianing Liu; Mingzhen Xu; Tingqi Zhu; Shuangxing Liu; Pingquan Liu; Huayuan Liu; Shi Tang; Zhunan Li; Weiwei Jin; Donghua Li; Yadong Tian; et al. (BMC Genomics)
Abstract Background Spermatogenesis is a pivotal biological process for the precise transmission of paternal genetic information, governed by a highly complex and dynamically regulated testicular microenvironment. Although mammalian research has characterized germ cell development at the single-cell level, differences in reproductive strategies limit the relevance of these findings to avian species. Results We employed single-cell RNA sequencing (scRNA-seq) to analyze the testes of the “Yufen 1” H line roosters at five distinct developmental stages: birth, rapid testicular development, sexual maturity, physical maturity, and senescence. By constructing a single-cell transcriptomic atlas, we identified ten somatic cell subtypes and four germ cell subtypes, thereby elucidating the dynamic changes in gene expression during spermatogenesis. Notably, our findings indicate that meiosis initiates relatively early in chickens, with the formation of the blood-testis barrier being closely associated with pachytene spermatocytes. Additionally, the testicular microenvironment undergoes age-related adaptive changes. Furthermore, we observed that support cells at 20 and 80 weeks of age exhibit similar transcriptional profiles, while macrophages and T cells play a pivotal role in the formation of the testicular cords and vascular networks during the early developmental stages. Conclusion This study offers a comprehensive atlas of testicular development in chickens, elucidating the sequential cell fate transitions from spermatogonial stem cells to mature sperm, alongside the dynamic and intricate developmental trajectories of somatic cells within the testicular microenvironment. These findings present novel insights into avian testicular development and establish a theoretical foundation for future research in reproductive biology and breeding strategies.